Customer Loyalty Through Retailer Brand Equity: Perspectives from Male Alcoholic Beverage Consumers - Esinu Agordoh, Ms. Lovelace (International Journal of Scientific Research and Management (IJSRM), 2022)
The service business has risen to prominence in recent years as the primary driver of economic growth. As such competing organizations have consistently supplied higher service quality and a positive brand image to gain consumer pleasure and loyalty in the current competitive environment. The primary purpose of this study is to explore the motivational factors that enrich customer loyalty through retailer brand equity. The qualitative research method was used in the collection of data. Ten male consumers of alcoholic beverages were interviewed to solicit answers about their experiences with retail outlets during their purchases. In-depth, open-ended questions were asked during data collection. The findings reveal themes such as customer experience, brand trust, and customer satisfaction as customer motivations that enhance repurchase behaviours at the selected retail outlets. In addition, these motivational factors also show that retailer brand equity promotes customer satisfaction, which leads to customer loyalty.